Kebijakan Hukum Pidana terhadap Anak sebagai Pelaku Tindak Pidana Pembunuhan - Anggraini, Siti Rini; Almunawaroh, Sofa (ABDIMAS Iqtishadia, 2023)
The influence of technology is very damaging to children's lives if they are not able to use it properly. Various shows on television damage children's mentality. Lack of parental and other supervision is a motivating factor for children to commit criminal acts. Murder is a crime by taking the life of another person. The perpetrators of the crime of murder are still in the category of children, so the very special arrangement through the juvenile justice system is a special consideration. This study aims to examine the regulation of criminal law against the crime of murder and examine criminal law policies against children as criminal offenders in the future. This research uses normative law, with a statutory and conceptual approach. Sources of data used are primary and secondary legal data collected by recording. After the data was collected, it was then analyzed descriptively qualitatively. The results of the study indicate that the form of the crime of taking another person's life  can be in the form of intentional (dolus) andunintentional (negligent). The arrangements are regulated in Articles 338 of the Criminal Code to Article 350 of the Criminal Code. Criminal law policies against children as perpetrators of criminal acts are regulated by a juvenile criminal justice system by prioritizing restorative justice through penal policies and non-penal policies.